2014
DOI: 10.1111/rda.12346
|View full text |Cite
|
Sign up to set email alerts
|

Husbandry Factors and the Resumption of Luteal Activity in Open and Zero‐Grazed Dairy Cows in Urban and Peri‐Urban Kampala, Uganda

Abstract: ContentsThe study investigated the influence of selected husbandry factors on interval to resumption of post-partum cyclicity among dairy cows in urban and peri-urban Kampala. A prospective study of 85 day post-partum period of 59 dairy cows in open (n = 38) and zero grazing (n = 21) systems was conducted on 24 farms. Cows of parity 1–6 were recruited starting 15–30 days post-partum. Progesterone (P4) content in milk taken at 10–12 day intervals was analysed using ELISA. The cow P4 profiles were classified int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In Uganda, a study (Kanyima et al, 2014) revealed that up to 81.4% of dairy cows in peri-urban Kampala resumed cyclicity within 60 days post calving. However, only 23.7% of the daily cows maintained cyclicity and were therefore the only ones that could achieve the recommended 365-day calving interval.…”
Section: Pathological Postpartum Cycling Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Uganda, a study (Kanyima et al, 2014) revealed that up to 81.4% of dairy cows in peri-urban Kampala resumed cyclicity within 60 days post calving. However, only 23.7% of the daily cows maintained cyclicity and were therefore the only ones that could achieve the recommended 365-day calving interval.…”
Section: Pathological Postpartum Cycling Patternsmentioning
confidence: 99%
“…It is important to note that studies on management causes of sub-optimum reproductive performance especially general husbandry practices have been the most emphasized in Uganda. Kanyima et al (2014) reported management errors that include calving in unhygienic environments, manual extraction of cow placentae shortly after calving and traditional practices of managing obstetrical cases among dairy farmers in peri-urban Kampala. These practices predispose to post parturient disorders such as endometritis, metritis and retained afterbirth, all which adversely affect reproductive performance of dairy cows.…”
Section: Dairy Farm and Herd Management Errorsmentioning
confidence: 99%
“…Consequently, high yielding cows will experience some degree of NEB during the early postpartum period (25). NEB induces excessive tissue mobilization, primarily of fat but also of protein, leading to subclinical and clinical ketosis and fatty liver (20).…”
Section: Effect Of Dietary Proteinmentioning
confidence: 99%